Peran Kampus Mengajar Dalam Meningktakan Literasi Dan Numberasi Di SD N 34 Kota Bengkulu - Herlena Nofita; Fahmi Lubis; Septina Lisdayanti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Campus Teaching Activity 3 is a service activity in the world of education. Campus teaching activity 3 in 2022 focuses on literacy and numberation, one of which is carried out at SDN 34 Bengkulu City. The aim is to improve students' understanding in understanding literacy and numberation. The results obtained are that the students of SDN 34 Bengkulu City still lack understanding of students in participating in literacy and numbration learning activities. This proves that there are still students who cannot read and count. This is because there are several influencing factors such as the lack of teacher innovation in increasing student interest in learning, students are polluted with online games, facilities and infrastructure supporting learning are still lacking. In this case, what we do to improve understanding of literacy and numberation is to innovate learning so that students are interested in participating in the learning process carried out by the teacher, and provide homework (PR) to each student so that the lessons learned in class can be reviewed.